MULTI-INFARCT DEMENTIA - Diandra Sari, Ayu; Ratep, Nyoman; Satriyasa, Bagus Komang (Bali Journal of Medical and Health Sciences; vol 1no1 2013)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 D e mentia is a c o g ni t ive functio n al d e fi c i t s that ca uses memo r y i m p a irme n t with s y mp t oms such a s: a ph a sia, a g nosi a , a p ra x ia or a dis t u r b a n c e in e x ec ut i ve fun c t i oni n g (the a bi l i t y to plan, sequence, a nd o r g a ni z e ) that in t e r fe r e s with s o c ial, o c c up a t i on a l, or in t e rp e rson a l ski l ls. Most of d e mentia a mo n g ol d e r p e ople in Asi a , es p e c i a l ly I ndon e sia is V a s c ular d e mentia. M ost of v a s c ular d e mentia a mong older p e ople in I ndo n e sia is mu l t i - inf a r c t d e mentia ( M I D ) . Mult i - inf a r c t d e mentia ( M I D ) is a dis o rd e r invo l ving d e te r ior a t i on in m e ntal f un c t i on ca used b y c h a n g e s or d a m a g e to the b r a i n t i ssues f r om la c k of o x y g e n a s a r e s u lt of mu l t i p le blood c lo t s throu g hout the b ra in. Risk f a c tor for M I D include a his t o r y o f: H a rd e ni n g o f a r t e ri e s ( a rth r os c l e r osis), h i g h b lood p re ssure ( h y p e rt e nsion), smokin g , a nd stro k e . I n M I D, dis r upt i on of blood flow le a d s to d a m a g e d b ra in t i ssue. F or di a g no s e the p a t i e nt with M I D, t he most i m port a nt th i ng we must do is a n a mnesis. F rom a n a mnesis, we ca n g e t his t o r y of su f fi c ient e x posur e , Ons e t of s y mp t oms, c h ec ki n g sign a nd doing tests, a nd a lso a sk wh e ther the p a t ie nt h a s risks f a c tors a bout M I D or not. Th e re is no known d e finit i ve tr ea t m e nt for M I D. T rea t m e nt is b a s e d on c ontrol of s y m p to m s. Oth e r tr e a t m e nts m a y be a dv i s e d b a s e d on t he ind i vidual c ondi t ion . /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}